Repair of Bland-White-Garland Syndrome via a Modified Technique - Manoly, Imthiaz (Texas Heart Institute, 2014)
Surgically repairing Bland-White-Garland syndrome (anomalous origin of the left coronary artery from the pulmonary artery) is a challenge if there are variations in the origin of the anomalous artery. We report the successful repair of this congenital abnormality in a 19-year-old woman who presented with an acute anterior myocardial infarction. The anomalous artery originated from the anterior-facing sinus of the pulmonary artery, which precluded typical repair by direct reimplantation or fashioning an intrapulmonary tunnel. We created an extrapulmonary tunnel, using a strip of pulmonary artery anteriorly and an aortic flap posteriorly. Three years postoperatively, the anastomosis was patent and the patient was asymptomatic. Our modified technique might serve as an alternative method during similar surgical circumstances.